Transthoracic ultrasonography for the immunocompromised patient. A pilot project that introduces transthoracic ultrasonography for the follow-up of hematological patients in Romania - Frinc Ioana; Ilies Petru; Zaharie Florin; Dima Delia; Tanase Alina; Petrov Ljubomir; Irimie Alexandru; Berce Cristian; Lisencu Cosmin; Berindan-Neagoe Ioana; Tomuleasa Ciprian; Bojan Anca (Sciendo, 2017)
In the past decade, there has been significant progress in clinical hematology with the discovery of targeted molecules and thus the achievement of both hematologic and molecular responses. Nevertheless, chemotherapy remains the treatment of choice for many types of hematological malignancies. Aggressive chemotherapy leads to immunosuppression, accompanied by a high rate of infections and an increased rate of treatment-related mortality. Invasive fungal infections as well as more common bacterial and viral infections are frequent in immunocompromised patients as they are difficult to diagnose and treat. Pleuropulmonary infections in immunocompromised patients are diagnosed using clinical examination, imaging and laboratory tests. Many laboratory tests are run for several days before a final result is given and are expensive. Computer tomography is a reliable technique, but it is encumbered by high irradiation and high cost, and can assess lesions larger than 1 cm. Transthoracic ultrasound is a modern method, used in the diagnostic algorithm of pleuropulmonary pathology. It allows the diagnosis of small lesions, can be performed at the patients' bedside, with acceptable costs and no irradiation. A fast, informed and accurate medical decision is essential for a favorable outcome in immunosuppressed patients with an adjacent infection. In the current case series we present the implementation of a new protocol for the follow-up of immunocompromised patients using transthoracic ultrasonography, of great potential use in the clinic.